Efetifitas Modifikasi Bola Karet terhadap Hasil Shooting dalam Pembelajaran Permainan Bola Tangan: Penelitian Tindakan Kelas pada Kelas X SMA Negeri 15 Surabaya - Hayati Hayati; Hanipah Hanipah; Ardhana Hari Pangestu; Aris Joko Cahyono; Favian Revananda; Diah Novita Anggraini; Hafish Adji Prasetya; Eko Yulianto; Bambang Yudi Erwanto (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Limitated of infrastructure is one of the issues affecting the continuity of education in Indonesia. The unequal distribution of facilities in schools undoubtedly makes the learning process less effective and impacts students' learning outcomes. This is particularly evident in physical education, sports, and health lessons, which require equipment for the learning process. The lack of equipment prevents the expansion of sports education and the introduction of other sports as part of the curriculum. One example is handball, which is rarely taught in schools due to the lack of balls. As a result, some schools resort to using other balls, such as volleyballs, to teach handball. Using a volleyball in handball lessons is ineffective, especially when it comes to shooting. This issue led the researcher to consider modifying the handball with a rubber ball, which is easy to find and resembles the size of a real handball. The researcher then implemented this modification in a two-cycle action research study. The results from the pre-cycle assessment showed that only 2 out of 35 students passed the shooting test. In terms of percentage, this means only about 6% of the students were able to shoot well. Following this, the researcher took action in the first cycle, and 19 students passed, about 54% of the sample. Since the results were still considered suboptimal, the researcher proceeded with the second cycle, where 32 students passed, around 91% of the sample.